Microarray image and data analysis : theory and practice - Rueda, Luis (Boca Raton : Taylor & Francis, 2014)
'Microarray Image and Data Analysis: Theory and Practice is a compilation of the latest and greatest microarray image and data analysis methods from the multidisciplinary international research community. Delivering a detailed discussion of the biological aspects and applications of microarrays, the book:Describes the key stages of image processing, gridding, segmentation, compression, quantification, and normalizationFeatures cutting-edge approaches to clustering, biclustering, and the reconstruction of regulatory networksCovers different types of microarrays such as DNA, protein, tissue, and low- and high-density oligonucleotide arraysExamines the current state of various microarray technologies, including their availability and affordabilityExplains how data generated by microarray experiments are analyzed to obtain meaningful biological conclusionsAn essential reference for academia and industry, Microarray Image and Data Analysis: Theory and Practice provides readers with valuable tools and techniques that extend to a wide range of biological studies and microarray platforms'--
Includes bibliographical references and index.
Keywords: Biotechnology -- Data processing; Protein microarrays; Image processing